Enhanced transdermal delivery of lidocaine cream via ultrasound and microneedle rollers - Sun, Jiaxiao; Yang, Yang; Zheng, Juanjuan; Liang, Hao; Yan, Feng; Zhang, Wensheng; Xie, Wenqin (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveThe aim of this study is to determine the most effective physical parameters for optimizing the transdermal delivery of lidocaine cream.MethodsPreliminary experiments were conducted to optimize ultrasound settings while ensuring safety, guided by visual and histopathological evaluations following observations of skin burns in rats. Ex vivo assessments of lidocaine penetration into isolated porcine ear tissue were conducted using Franz diffusion cells and confocal laser scanning microscopy under different intervention conditions In vivo analysis involved measuring lidocaine concentrations in rat skin following treatments combining ultrasound and microneedle rollers. The anesthetic efficacy of these interventions was further assessed using the “rat tail-flick test.”ResultsTwelve non-invasive parameter configurations involving ultrasound and microneedle rollers were identified. The combination of ultrasound and microneedle rollers yielded superior results while the ultrasound-only groups demonstrated improved diffusion compared to the control. Notably, ultrasound applied at 260 kHz with a 90% duty cycle, in conjunction with microneedle rollers, achieved the highest diffusion rates, with ex vivo cumulative lidocaine permeation at 15 min reaching 45.81 ± 4.19 μg/cm2 (vs. baseline 60 min value, p = 0.0017) and microneedle roller alone at 48.62 ± 6.73 μg/cm2 (p < 0.0001). Confocal laser scanning microscopy demonstrated minimal lidocaine penetration without interventions, whereas the combined ultrasound and microneedle approach resulted in significantly enhanced penetration, with visible fluorescence deep in the dermis within 5 min. In vivo findings corroborated these results, with the combined method facilitating the most rapid onset of anesthesia (mean onset time 28.75 ± 6.41 min, p < 0.05 vs control 67.50 ± 4.63 min) and improved transdermal delivery compared to other groups, achieving 100% anesthetic efficiency rate at 60 min vs. 25% in control.ConclusionMicroneedle rollers demonstrate superior clinical efficacy over ultrasound, enabling rapid lidocaine delivery (15-min onset ex vivo; 32.5-min anesthesia in vivo) and achieving 100% anesthetic efficiency for time-sensitive procedures—establishing a practical paradigm shift in transdermal local anesthesia.